Demographic profile and perceived in-service education and training needs of rural and township physical science teachers in the Limpopo province. - Mabye, Daniel Tlabo (School of Education, 2023)
The Limpopo Province is characterised by poor Physical Science matric results and poorly qualified teachers. There are many reasons which contribute to the poor Physical Science matric results such as for example, lack of equipment and poverty in this largely rural area. Effective INSET programmes however, can be a possible solution to improving teachers' qualifications and competencies. The success of INSET programmes basically depends on obtaining and utilzing information on demographic profiles and perceived INSET needs of Physical Science teachers. Unfortunately, there is a lack of information on the demographic profile and perceived INSET needs of Physical Science teachers in the Limpopo Province. This study aims at collecting and analysing data, which will provide information on the demographic profile and perceived INSET needs of Physical Science teachers in the Limpopo Province. It is anticipated that the availability and utilisation of this information will hopefully contribute to the improvement of Physical Science education in the Limpopo Province. The objectives of the study are reflected in the following rese:R[ch questions: a) What is the demographic profile of Physical Science teachers in the Limpopo Province? b) What are the perceived INSET needs of Physical Science teachers in the Limpopo Province? c) What are the possible associations between the demographic profile and perceived INSET needs of Physical Science teachers in the Limpopo Province? Two methods were used to elicit the demographic profile and perceived needs of Physical Science teachers, namely the survey method using a pencil-and-paper instrument-the Science Teachers Inventory of Needs-Northern Province (STIN-NP}-which was specially adapted and validated for this purpose, and focus group interviews with Physical Science teachers. 'The STIN-NP was developed from the Science Teachers Inventory of Needs (STIN3) of Baird, Prather, Finson and Oliver (1994). The STIN-3 was adapted and validated for use in the Limpopo Province context by inviting 47 important stakeholders in Physical Science education at provincial and national level to suggest modifying, omitting or adding items to STIN-NP and to provide a rationale for their suggestions. Items in the instrument were thereafter modified for clarity and ambiguity by an English Second Language expert. STINNP was thereafter piloted on tlrree samples of Physical Science teachers from urban, township and rural schools (n=29) in the Limpopo Province. iv The final version of the STIN-NP consists of 98 items arranged in six sections. Information on the reliability of STIN-NP was determined by calculating the items' alpha coefficient and the instrument's Guttman split-half reliability coefficient after the instrument had been administered. The alpha coefficient reliability for use of with Physical Science teachers was 0 .95, and the adjusted Guttman split-half reliability was O .83. A total of 1629 questionnaires were distributed to Physical Science teachers in the Limpopo Province via District Office's Curriculum Advisers and school principals. Completed questionnaires were collected from teachers via the same way. Focus group interview questions were structured to cross-validate the information obtained through the questionnaires and also to help acquire possible additional information on the teachers' INSET needs. The total number of Physical Science teachers who responded to the invitation for the interviews were 35 (18 male teachers and 17 female teaches) in six groups. The six groups were from urban, rural, and the township areas as it was assumed that INSET needs were largely influenced by school context. Interviews were recorded and later transcribed into a more formal and written style in order to facilitate analysis of what was said by the interviewees, as recommended by Kvale (1996: 170). The quantitative results of this study are based on the responses of 352 Physical Science teachers (grades 10-12) in the Limpopo Province--a 22% response rate. Only eight responses were received from teachers at urban schools, but these responses were ignored as this sample is too small to enable the researcher to draw conclusions about urban teachers with confidence. The effective sample used in the analysis is thus 344, comprising 300 rural and 44 township teaches. Professionally, teachers need help with improving their teaching skills, followed by improving content knowledge, classroom organisation and assessing learners' work. The above ranking is the same for both rural and township teachers. The above ranking also suggests that INSET providers should focus on improving teaching skills and content knowledge of teachers first, and only later on for example, assessment. Physical Science teachers finther indicated that they need help with carrying out laboratory practicals. These teachers' limited academic knowledge and the lack of textbooks suggest that INSET providers should aim at empowering these teachers to improvise equipment and learning and teaching materials. The fact that most teachers have limited academic knowledge suggests that a suitable INSET model for them, will be Dunn's traditional model which will assist them to gain additional qualification (Nduna, 1999). V Most of the Physical Science teachers failed to attend the workshops due to lack of information (Table 4. 5 page 36). INSET providers should issue a year programme in time to reach all Physical Science teachers. Physical Science, Mathematics and Biology workshops should not take place simultaneously, so that learners are not left unattended, and some teachers also teach all three subjects. The Department of Education in the Limpopo Province is urged to provide workshops based on practical sessions in Physical Science and how to improvise equipment. This will help to restore learners' interest and understanding of science. Establishing and staffing resourcecentres in various districts will help many schools without equipment. INSET programmes for Physical Science should be guided by teachers' professional needs in order to be more appropriate, sustainable and effective. Workshops should be conducted at a convenient time and venue for teachers. It is anticipated that the established perceived needs of Physical Science teachers in the Limpopo Province as described and stated above will provide an important, valid and reliable basis for designing effective, and sustainable programmes for Physical Science in the Limpopo Province. It is also hoped that such programmes will significantly facilitate attempts to improve Physical Science education in the Limpopo Province. KEYWORDS: In-service education and training, (INSET), Interviews, Science Teachers, Needs Assessment, Limpopo (Northern) Province, Rural Areas, Surveys, Teacher Characteristics, Test Construction.